Ghana : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This Selected Issues paper on Ghana shows that as a small, open low-income economy, the country faces several major challenges in its conduct of disinflation policy. Ghana has historically experienced volatile and often high inflation rates. The paper also presents a model that recognizes difficulties being faced by Ghana, among them less-than-perfect credibility of announcements of inflation reduction and policymaker aversion both to movements of output from its potential level and to variability in the interest rate.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet